(untitled) (Baghdad Science Journal, 2025)
The inhibition effect of crude juice of green and black olive on cancer cell line (RD) in vitro has been studied by depending on micro titration system . Eleven different concentration starting from (916-960) mg/ml of crude juice respectively ,for three periods of exposure(24-48-72)hours. The resulted showed that the inhibition effect dependent on type of olive fruit juice ,concentration of dose ,time of exposure and the high concentration of both type of olive juice increased the growth of cell line while other concentration caused decrease in different rates ,moreover the black juice was more effective than green and 48 hours’ time exposure was the best for inhibition.